Establishment of an in vitro screening model of bioactive compounds from Vietnamese medicinal plants using the recombinant central nervous system receptors - Nhung, Pham Thi Hong; Long, Dinh Doan (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 1, 2018)
The central nervous system receptors are important targets of the drugs, involved in many neurological diseases. Therefore, this study was designed to build an in vitro screening model using recombinant receptors distributed in the central nervous system (CNS). Method: construction of cDNA system encoding for receptors; using Semliki Forest virus for the rapid and high expression of receptors in mammalian cell lines; designing binding assays for in vitro pharmacological studies of compounds and methanol plant extracts. Results: 24 cDNAs encoding for receptors and 1 screening kit with neurokinin-1 receptor were constructed; 4 receptors were expressed successfully. Conclusion: The in vitro screening model was established successfully and applied for NK1 receptors with high sensitivity and specificity. This model is a useful tool for discovery and development of target compounds acting in the CNS.   Keywords Recombinant CNS receptors, an in vitro screening assays, bioactive compounds, Semliki Forest virus. specificity References [1] Đỗ Huy Bích và cs, Cây thuốc và động vật làm thuốc ở Việt Nam, NXB Khoa học và kỹ thuật, 2004 [2] Kenneth H. Lundstrom, M.L. Chiu, G Protein - Coupled receptors in Drug Discovery, Taylor & Francis Group, 2006 [3] Zhu M., Bowery N.G., Greengrass P.M., Phillipson J.D., Application of radioligand receptor binding assays in the search for CNS active principles from Chinese medicinal plants, J. Ethnopharmacol. 54 (1996) 153 [4] Phạm Thị Hồng Nhung, Hoàng Thị Mỹ Nhung, Đinh Đoàn Long, Cải biến vectơ hệ Virus Semliki Forest (SFV) nhằm biểu hiện thụ thể GPCR của người Việt Nam, Tạp chí Khoa học ĐHQGHN: Khoa học Tự nhiên và Công nghệ 31 (2015) 47 [5] Berglund P., Sjoberg M., Garoff H., Atkins G.J., Sheahan B.J., and Liljestrom P., Semliki Forest virus expression system: production of conditionally infectious recombinant particles, Biotechnology 11 (1993) 916 [6] Dinh DL, Pham THN, Hoang TMN, Trinh TC, Vo TTL, Pham TH, Kenneth L., Interaction of Vietnamese medicinal plant extracts with recombinantly expressed human neurokinin-1 receptor, Planta Medica Letters, 2(2015)42 [7] Rosso M., Mu᷈ Noz M., Berger M., The Role of Neurokinin -1 Receptor in the Microenvironment of Inflammation and Cancer, The Scientific World Journal, 2012 (2012)1 [8] Tô Việt Bắc, Bùi Minh Đức, Phạm Thị Kim, Thử nghiệm khả năng gây độc trên chuột của chế phẩm rotundin, Tạp chí Y hoc Việt Nam, 7(1994)46 [9] Violin J.D., Crombie A.L., Soergel D.G., Lark M.W., Biased ligands at G-protein-coupled receptors: promise and progress, Trends Pharmacol Sci, 35(2014) 308 [10] Lundstrom K., Henningsen R., Semliki Forest virus vectors applied to receptor expression in cell lines and primary neurons, J. Neurochem 71 (1998) [11] Federal Register 58 No. 19, Addition of Appendix DL-X to the NIH guidelines regarding Semliki Forest virus. Human Gene Therapy. 1993. p.5.